The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0134690
|View full text |Cite
|
Sign up to set email alerts
|

Human Serum Albumin Increases the Stability of Green Tea Catechins in Aqueous Physiological Conditions

Abstract: Epicatechin (EC), epigallocatechin (EGC), epicatechingallate (ECG) and epigallocatechingallate (EGCG) are antioxidants present in the green tea, a widely used beverage whose health benefits are largely recognized. Nevertheless, major physicochemical limitations, such as the high instability of catechins, pose important questions concerning their potential pharmacological use. Recent studies indicate that binding of catechins with plasmatic proteins may modulate their plasma concentration, tissue delivery and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…Catechins are generally most stable in solution at a pH range of 4-6. It is now known that human serum albumin acts as a stabilizer, binding to the catechins and then transporting them [ 50 ]. Various studies in humans have found that the peak concentrations of catechins and their metabolites occur in blood plasma between 1.5 and 2 hours after ingestion and in urine between 4 and 6 hours after ingestion.…”
Section: Green Tea Compositionmentioning
confidence: 99%
“…Catechins are generally most stable in solution at a pH range of 4-6. It is now known that human serum albumin acts as a stabilizer, binding to the catechins and then transporting them [ 50 ]. Various studies in humans have found that the peak concentrations of catechins and their metabolites occur in blood plasma between 1.5 and 2 hours after ingestion and in urine between 4 and 6 hours after ingestion.…”
Section: Green Tea Compositionmentioning
confidence: 99%
“…4b). Because EGCG binds to serum albumin [37], possibly diminishing cellular uptake, we repeated the LC-MS experiment, but now cultured cells in serum-free medium. Under these conditions, EGCG treatment resulted in a significant reduction of 13 C- flux from *Glu to D- 2-HG (Additional file 1: Figure S1).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Anticancer effects of EGCG can be diminished due to oxidation of the compound [66], resulting in low circulating doses after oral administration [67, 68]. Furthermore, EGCG in the circulation is mostly albumin-associated, increasing stability but decreasing bioavailability [37]. Methods to increase bioavailability via nanomedicine and controlled delivery are currently being explored [69, 70].…”
Section: Discussionmentioning
confidence: 99%
“…In part, this is due to EGCG high solubility, which limits its absorption through membranes and in part to its chemical steadiness, that is elevated in an acidic environment such as the stomach during gastric digestion, but decreases rapidly in alkaline duodenal environments [ 81 ]. The wide distribution of EGCG in most tissues is explained by its avid binding to albumin, which stabilizes and transports EGCG in the bloodstream [ 82 ]. In humans, as in mice, EGCG undergoes similar phase II biotransformation processes that result in methylated, sulfated and glucuronidated products as the major EGCG metabolites [ 83 , 84 ].…”
Section: Structure Of Egcg: Is An “Antioxidant” or “Pro-oxidant” Mmentioning
confidence: 99%